Monolithic Integration of Collimating Fresnel Lens for Beam Quality Enhancement in Tapered High Power Laser Diode - Lau, F. K. (Institutional Knowledge at Singapore Management University, 2006)
We demonstrate, for the first time, a monolithic integrated lens for wide aperture gain-guided tapered laser beam quality enhancement by compensating the quadratic phase curvature. The 3mm long tapered laser with an output aperture of 170μm adopted in this design consists of a gain-guided tapered section and an index-guided ridge section and operated at 980nm. The lens design is implemented by focus ion beam etching (FIBE) technique, whereby the laser diode is mounted p-side up in order to facilitate the etching process. The lens is located 600μm away from the junction of the tapered and ridge sections, and is 40μm wide and 300μm long with a focal length of 800μm. The laser diode is characterised by light-current characteristics together with near- and far- field measurements before and after etching. The device is biased by current pulses of 1μs width and 0.1% duty cycle. Light-current measurement shows a drop of 10.5% in threshold current from 380mA to 340mA after the inclusion of lens. This is an evidence that the lens effectively equalised the curved phase in order to reduce the laser cavity loss by improving the coupling efficiency of backward travelling wave at the output facet. Throughout the whole current range tested, the width of near-field at waist is broadened by an average of 36% after the inclusion of lens. By successfully compensating the quadratic phase curvature of the mode, the beam divergence in the far-field is significantly narrowed by an average of 28.5%. M2 factor is improved by an average of 12%.